National Program for Strengthening Family Farming: Promotion of Family Farming or Agribusiness in Brazil? - Trentin, Iran Carlos Lovis (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2019)
The objective of this article is to discuss, as the PRONAF (National Program for Strengthening Family Farming) while it is a public policy of "Strengthening Family Farming" has contributed to the increase in the production of merchandise (commodities for export) in predominant areas of family farmers. Therefore, an investigation was carried out in areas of family agriculture not north of Rio Grande do Sul in 2017-18. Where, they will analyze some considerations on the agrarian structure, as well as the data of increase of the productivity and the area used in the production of the main export crops in the years 2000-2017. And also some considerations of the rural surroundings how this model of agriculture has degraded the environments, especially with the increase of the rates of application of pesticides to each year in Rio Grande do Sul and Brazil. As a result, it was observed that this model based on significant public financing has maintained rural poverty, indebtedness and dependence on some regions with strong primary production at the expense of other more industrialized regions. Finally, we present a discussion on the need to review the role of public policies that promote food security, recovery and environmental protection by promoting agroecology in areas with the presence of poor farmers in Brazil.